Natural orbital functional theory and pairing correlation effects in electron momentum density: Электронная структура и Ферми поверхность - Barbiellini, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Occupation numbers of natural orbitals capture the physics of strong electron correlations in momentum space. A natural orbital density functional theory based on the antisymmetrized geminal product provides these occupation numbers and the corresponding electron momentum density. A practical implementation of this theory approximates the natural orbitals by the Kohn–Sham orbitals and uses a mean-field approach to estimate pairing amplitudes leading to corrections for the independent particle model. The method is applied to weakly doped La2CuO4.